1999
DOI: 10.1111/j.1469-7793.1999.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient, reversible apnoea following ablation of the pre‐Bötzinger complex in rats

Abstract: The rhythmic alterations of cranial and spinal nerves which are characteristic of eupnoeic ventilatory activity are dependent upon two interrelated processes. Neuronal mechanisms within the pontile and medullary brainstem are responsible for generating the eupnoeic rhythm. For this rhythm to be expressed in activities of cranial and spinal nerves, a level of tonic neuronal input is required (e.g. Euler, 1986;St-John, 1998a). Thus, eupnoea could be eliminated following ablation of neurons which are responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
4
30
1
Order By: Relevance
“…These data led to the conclusion that the neurogenesis of eupnea is within rostral pontine nuclei (53). This conclusion is supported by data showing that chemical destruction of the preBötC in vivo only transiently eliminated respiratory rhythm (51). Moreover, data from other studies have shown that a pontine-medullary circuit is necessary for the three-phase eupneic respiratory rhythm and that the medulla in isolation is only capable of generating the gasping rhythm (48,52,53).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These data led to the conclusion that the neurogenesis of eupnea is within rostral pontine nuclei (53). This conclusion is supported by data showing that chemical destruction of the preBötC in vivo only transiently eliminated respiratory rhythm (51). Moreover, data from other studies have shown that a pontine-medullary circuit is necessary for the three-phase eupneic respiratory rhythm and that the medulla in isolation is only capable of generating the gasping rhythm (48,52,53).…”
Section: Discussionsupporting
confidence: 68%
“…Likewise, based on data from carbachol-induced rapid-eye-movement (REM) sleep and in vitro studies, it has been hypothesized that direct and indirect excitatory M 2 receptor modulation of hypoglossal motoneurons maintains a patent upper airway during REM sleep (4,5). Furthermore, strong support for a role for mAChRs in respiratory rhythmogenesis comes from studies using a medullary slice preparation from neonatal rats that found that local application of ACh excites 88% of inspiratory neurons within the pre-Bötzinger Complex (preBötC), a site critical for respiratory rhythm generation in some (55,57), but not all (51,53), studies. These preBötC responses to ACh were blocked by atropine and by specific blockers of M 3 receptors, but not by specific blockers of M 1 , M 2 , or M 5 receptors, leading to the conclusion that ACh is excitatory to preBötC neurons (45,46), likely through the activation of postsynaptic M 3 receptors.…”
mentioning
confidence: 99%
“…There is substantial evidence pointing to the importance of specific neuronal groups within the ventral medulla. The pre-Bötzinger complex (preBötC) contains cholinergic neurons[10] and is integral to normal respiratory function[11]. Other sites in the ventral region of the medulla are involved in respiratory control and contain cholinergic synapses, including the ventral surface of the medulla[12], the nucleus ambiguus[13] and the retrotrapezoid nucleus[14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the return of eupnoea was not due to actions of remnants, if any, of the pre-Bö tzinger complex but rather to a reorganization of the pontomedullary neuronal circuit for eupnoea. Importantly, gasping was eliminated irreversibly following these perturbations of the pre-Bö tzinger complex (St Jacques & St John 1999).…”
Section: Rhythms Of In Vitro Preparationsmentioning
confidence: 99%